Factors Influencing Language Learning in Didactic Audiovisual Translation Within the TRADILEX Project - Paula Buil-Beltrán; María Bobadilla-Pérez (Profile: Issues in Teachers' Professional Development)
This paper reports a mixed-method study on the factors shaping language learning through didactic audiovisual translation. The aim is to analyse the determinants influencing the effective implementation of an integrative project, revealing the strengths and weaknesses of the learning process. Data from 172 students were gathered through initial and final questionnaires, which offered insights into their perceptions of didactic audiovisual translation. The results demonstrate a noticeable shift in learners’ attitudes towards audiovisual translation as a language learning tool during the tasks. This transformation led to the recognition of potential benefits, not only in conventional modes like subtitling and dubbing but also in less recognised modes such as audio-description and subtitling for the deaf and hard of hearing.